Smart city development: Data sharing vs. data protection legislations - Joyce, Aaron; Javidroozi, Vahid (Cities, 2024)
Fuelled by cutting-edge technology, smart cities offer vast potential to enhance urban living, elevate service delivery, and foster sustainability. Central to this digital transformation is seamless data exchange across city sectors like transportation, healthcare, energy, education, and so on. However, stringent data protection laws pose a significant hurdle to cross-sectoral data sharing in smart cities. This study explores the multifaceted aspects of cross-sectoral data sharing within smart cities. It investigates its significance, identifies barriers, and outlines prerequisites while navigating data protection regulations. The findings highlight a critical gap in the existing literature, emphasising the need for a comprehensive framework. Guided by a thematic analysis of insights from 14 interviews with expertise in smart cities, emphasising data-sharing and data protection legislation, this framework provides a systematic approach to enable cross-sectoral data-sharing in smart cities. It serves as a guide for urban planners and stakeholders. Following its initial development, the framework undergoes validation through interviews with six smart city experts. Their insights confirm the framework's robustness and efficacy in addressing the research question. Hence, this research advances the discourse on smart city development and offers a blueprint for balancing cross-sectoral data-sharing with data protection regulations, bridging the gap between innovation and compliance.